(untitled) (Asian Journal of Plant Biology, 2022)
Acrylamide contamination in food is mainly from raw material of plant-based origin. Acrylamide biodegradation by soil bacteria is an important remediation process. Bacillus sp. strain ZEID-14, which had previously been identified and exhibited the ability to break down amides, was examined further to determine the crucial parameters that contribute to the optimum growth of acrylamide. The Box-Behnken design was used to optimize the previously identified three significant components (pH, incubation time and acrylamide concentration). The model was supported by the diagnostic plots including the half-normal, Cook’s distance, leverage vs runs, residual vs runs, Box-Cox, DFFITS, and DFBETAS. Predicted optimal conditions were determined using "Numerical Optimisation" toolbox of the Design Expert software. Two optimal conditions were tested. The model predicted a maximum growth of 10.686 (95% C.I., 10.458 to 10.913) which was verified through experimental results with a growth of 11.257 (95% C.I., 11.051 to 11.462) with the actual results being near to the predicted values but was significantly higher than the predicted values. The second numerical optimization gave a solution with a predicted maximum growth of 9.305 Log CFU/mL (95% C.I. from 9.011 to 9.614) which was verified through experimental results with a growth of 9.978 Log CFU/mL (95% C.I. from 9.830 to 10.126) with the actual results were also significantly higher than the predicted values. The RSM exercise gave far better growth on acrylamide than OFAT with a higher response of about 2 log CFU/mL unit indicating the utility of RSM over OFAT in the optimization of growth of this bacterium on acrylamide.